Impact of flow inclination on downwind turbine loads and power. Issue 2 (September 2016) - Kress, C; Chokani, N; Abhari, R S; Hashimoto, T; Watanabe, M; Sano, T; Saeki, M
Abstract: Wind turbines frequently operate under situations of pronounced flow inclinations, such as in complex terrain. In the present work the performance and rotor thrust of downwind and upwind turbines in upward and downward flow inclinations are experimentally investigated. In an upward flow inclination of +13°, downwind turbines are shown to have a 29% larger power output than a corresponding upwind turbine, whereas the relative increase in rotor thrust is only 9%. Furthermore, it is also shown that the performance of downwind turbines is less sensitive to changes in the flow inclination, as the upstream nacelle on downwind turbines beneficially redirects and accelerates the flow around the nacelle into the rotor plane.